Loss prediction of induction motor using OPERA 2D software - Ismail, Daut, Prof. Dr.; Anayet, Karim; Pungut, Ibrahim; Yanawati, Yahya; Nor Shafiqin, Shariffuddin; Faizal (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.